Effects of pore size on the mechanical and biological properties of stereolithographic 3D printed HAp bioceramic scaffold. Issue 20 (15th October 2021) - Liu, Ruoxi; Ma, Lili; Liu, He; Xu, Baohua; Feng, Chengwei; He, Rujie
Abstract: In this study, hydroxyapatite (HAp) scaffolds with the pore size of 400, 500, and 600 μm were prepared by stereolithographic 3D printing (SL-3DP). The effects of pore size on mechanical and biological properties of the HAp scaffolds were investigated. Firstly, the macro- and microstructure of the HAp scaffolds were observed. Then, the compressive strength of the HAp scaffolds were tested. Finally, the biological properties of the HAp scaffolds were further characterized in vitro by the synthetic body fluid (SBF) solution immersion testing, as well as by using the cell proliferation and 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2H-tetrazolium bromide (MTT) assay. From this study, it was found that the HAp scaffold with a pore size of 600 μm had the most promising application prospect.